A rotary plasmonic nanoclock - Xin, Ling; Zhou, Chao; Duan, Xiaoyang; Liu, Na (Nature Communications, 2019)
Current DNA-assembled nanophotonic devices can only reconfigure among random or few defined states. Here, the authors demonstrate a DNA-assembled rotary plasmonic nanoclock in which a rotor gold nanorod carries out directional and reversible 360° rotation transitioning among 16 well-defined configurations.